2021
DOI: 10.1155/2021/8881557
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuroglial Crosstalk and Synaptic Plasticity-Mediated Central Sensitization in Acupuncture Analgesia

Abstract: Although pain is regarded as a global public health priority, analgesic therapy remains a significant challenge. Pain is a hypersensitivity state caused by peripheral and central sensitization, with the latter considered the culprit for chronic pain. This study summarizes the pathogenesis of central sensitization from the perspective of neuroglial crosstalk and synaptic plasticity and underlines the related analgesic mechanisms of acupuncture. Central sensitization is modulated by the neurotransmitters and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 142 publications
0
34
0
Order By: Relevance
“…Acupuncture, as an ancient Chinese medical technique, has been widely applied in the treatment of various types of pain over 3,000 years, and accumulating experimental and clinical studies have demonstrated its benefit for chronic pain during the last decade (Vickers et al, 2018;Gao et al, 2021). Numerous reviews have summarized the analgesic effects of acupuncture regarding the peripheral, spinal, and supraspinal mechanisms (Zhang et al, 2014;Lai et al, 2019;Lyu et al, 2021). Several studies indicate that peripheral opioids, induced by acupuncture, act on peripheral opioid receptors to desensitize peripheral sensory nerves and reduce pro-inflammatory cytokines peripherally (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture, as an ancient Chinese medical technique, has been widely applied in the treatment of various types of pain over 3,000 years, and accumulating experimental and clinical studies have demonstrated its benefit for chronic pain during the last decade (Vickers et al, 2018;Gao et al, 2021). Numerous reviews have summarized the analgesic effects of acupuncture regarding the peripheral, spinal, and supraspinal mechanisms (Zhang et al, 2014;Lai et al, 2019;Lyu et al, 2021). Several studies indicate that peripheral opioids, induced by acupuncture, act on peripheral opioid receptors to desensitize peripheral sensory nerves and reduce pro-inflammatory cytokines peripherally (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture inhibits the transmission of noxious inputs in the spinal cord with the involvement of spinal opioids, norepinephrine, serotonin, glutamate and glial cell (Zhang et al, 2014). Acupuncture analgesia is associated with downregulation of glutamate in the ascending excitatory pathway and upregulation of opioids, norepinephrine, and 5-hydroxytryptamine in the descending pain modulatory system, thus contributing to alleviate central sensitization (Lyu et al, 2021). From another perspective, affective disorders are interrelated with pain (Becker et al, 2018), and somatosensory pain memories may be revived after an amputation and lead to phantom limb pain (Katz and Melzack, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…P38, a member of mitogen-activated protein kinases (MAPKs), is an important downstream kinase of CX3CL1/CX3CR1 signaling [72][73][74]. Activation of CX3CL1/CX3CR1/p38 MAPK pathway induces synthesis of proin ammatory cytokines such as TNF-α and IL-6 in the microglia [74,75].…”
Section: Chemokine Cx3cl1 In Acc Mediates the Descending Facilitation And Aggravates The Spinal Neuroin Ammationmentioning
confidence: 99%
“…Acupuncture is involved in the modulation of neuroplasticity in the central nervous system [33] by raising the expression of neurotrophins such as brain-derived neurotrophic factor (BDNF) that increase synaptic transmission [33,34]. Acupuncture upregulates neurotransmitters such as norepinephrine, dopamine, and serotonin [33,35] and facilitates endogenous opioid mechanisms that modulate the pain pathways involved in neuroglial crosstalk and plasticity [36,37]. It reduces associated oxidative stress and apoptosis [36] and the action of inflammatory pathways, especially the toll-like receptor, and tumour necrosis factor (TNF) signaling pathways that activate the nociceptive neurons [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture upregulates neurotransmitters such as norepinephrine, dopamine, and serotonin [33,35] and facilitates endogenous opioid mechanisms that modulate the pain pathways involved in neuroglial crosstalk and plasticity [36,37]. It reduces associated oxidative stress and apoptosis [36] and the action of inflammatory pathways, especially the toll-like receptor, and tumour necrosis factor (TNF) signaling pathways that activate the nociceptive neurons [37,38].…”
Section: Introductionmentioning
confidence: 99%